The time-frequency method of signal analysis in internal combustion engine diagnostics; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Avramchuk V. S. Valery Stepanovich; Kazmin V. P. Viktor Pavlovich; Faerman V. A. Vladimir Andreevich; Le V. T. (2017, 2017)
Title screen